Mekanisme Infeksi Vibrio Pada Reseptor Ikan Kerapu Tikus Cromileptes altivelis [The Mechanism Of Vibrio Infection To Grouper Reseptor Cromileptes altivelis] - Uun Yanuhar (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract One of the most favourite fish that farmer fish cultivated because its high economic value was gouper (C. altivelis). The obstacle in cultivation system was caused by Vibrio algynolitycus. Vibrio angullarum, Vibrio parahaemolyticus. Vibrio harveyi infection. Many deseases that attacked to the grouper was caused by the role of pathogen specific as a ligan and its reseptor. The aim of these study was to improve and to know the role of reseptor in vibriosis mechanism with tested spesific reseptor protein of grouper Cromileptes altivelis. These study used experimental and descriptive methode with identified of grouper reseptor, Hemaglutinin test and observation use electron microscope. These study result showed that reseptor protein of C. altivelis was found in its eyes. These showed spesivity and reactivity to the vibriosis specific epitop.